Práticas pedagógicas apoiadas por tecnologias digitais : um estudo de caso no ensino fundamental - Guerra, Daniela Caon (2017)
This research aims to understand how the Digital Technologies are used as supportive elements in the teaching and learning processes of the students of 6th year of Elementary Education in a school that is characterized by encouraging the use of technological resources in the classroom. This research was intended to investigate which technological resources are being selected and how they are used pedagogically by the teachers investigated. For the development of this study the qualitative approach was adopted, through a Case Study from the perspective of Lüdke and André (2014) and Yin (2001). Semi-structured interviews and documentary research were used as instruments for data collection. For the analysis and data interpretation was used the technique of Content Analysis, proposed by Bardin (2009). The research subjects were 6th grade teachers of Elementary Education of a school belonging to the federal public network, located in Porto Alegre, Rio Grande do Sul. The study showed that among the technological resources most used in class are the computer, the Internet, video, digital image, datashow, smartphone and wiki, followed by audio, blog, games, notebook and digital platforms. Among the least used features are educational software, discussion forum and tablet. The research evidenced, among other aspects, that these resources are used in several situations in class, among them are: in the development of research projects; conducting research on the Internet or on search platforms; in the development of activities that involve the use of applications for editing text, image, audio, video or creation of presentations; for recording activities, recording and displaying videos; to share information, to display information from the computer or similar artifact, in lectures to work on content of images, films, among others. It is believed that with the mapping carried out through this investigation it will be possible to assist teachers who work in school with similar contexts to integrating Digital Technologies in their pedagogical practices, besides contributing to the studies of the area.